ANATOMICAL CHARACTERISTICS OF RICE PLANTS INFLUENCING RESISTANCE AND SUSCEPTIBILITY TO YELLOW STEM BORER (Biological Sciences - PJSIR, 2004)
Plant anatomical characters presumably influencing resistance and susceptibility to yellow stem borer (YSB) infestation were studied. Rice varieties having broader and thicker sclerenchymatous hypodermis, compact parenchyma cells of ground tissue, small air spaces in the ground tissue, more vascular bundles with narrower spaces between vascular bundles, ridged stem surface containing vascular bundles and narrower pith are considered to be characters for resistance. Whereas thinner sclerenchymatous hypodermis, loose parenchyma cells of ground tissue, larger spaces between vascular bundles, wider pith and larger air cavities, might be responsible for the susceptibility to (YSB). In the present study TKM6, BR1 and Nizersail were found to be resistant to (YSB), while TN1, IR8, BR3, BR4 and BR14 were susceptible varieties.